Optical wireless links with enhanced linearity and selectivity [Invited] - Green, Roger J.; Sweet, C.; Idrus Sutan Nameh, Sevia Mahdaliza (Optical Society of America, 2005)
Optical wireless is an attractive medium as an alternative to optical fiber communications, and also to RF, because of its high bandwidth and relative ease of use, especially when it comes to deployment in new physical situations. We describe an optical wireless link approach that offers a performance that gives analog transmission with significantly reduced distortion levels and enhanced reception sensitivity by combining a novel hybrid detector-amplifier technique. Reduction of distortion by 40 dB and improvement in sensitivity of 20-30 dB is possible, using the techniques described. Â© 2005 Optical Society of America.